Asean Against Cyber Terorrism: Upaya Mengatasi Propaganda Hitam Sebagai Kejahatan Siber Terorganisir - Nur Qalbi. S; Fitrah Marinda; Rina Yulianti (Jurnal Legislatif, 2020)
Abstract: The development of information and information in the race of the less than 41s not only provide access to the ease for the community, but also followed by the emergence of a new number of threats. Along with the benefits, cyber technology also has a negative impact and opportunity for people who are not responsible for conducting cyber crime. One of the issues that are big challenge and the current international problems are terrorism. This terrorism act has even been done through technology and is included in one typeof cyber crime is cyber terrorism. The terrorist group makes social media as one of the media to spread their terror propaganda. In analyzing, the method used by the author is a qualitative research method. This method is more prioritizing on process problems and meaning/preceptions so that it can reveal various qualitative information with descriptive-analysis of through and does not reject quantitative information in the form of numbers and numbers. Against this issue, the authors conclude ASEAN Against Cyber Terrorism concept to resolve the existing issues. This paper provides a more detailed analysis of two important points. First, against the completion of the issue of black propaganda issues that are disseminated through social media that is currently performed by ASEAN. Second, explanation and implementation of the ASEAN Against Cyber concept is territorial to apply in addressing black propaganda by terrorist groups through social media. Keywords: ASEAN; Cyber Terrorism; Social Media; Black Propaganda; Abstrak Perkembangan teknologi dan informasi di era 4.0 yang kian pesat tidak hanya memberi akses kemudahan bagi masyarakat, namun juga diikuti oleh munculnya sejumlah ancaman baru. Seiring dengan manfaatnya, teknologi siber juga memberi dampak negatif dan kesempatan bagi orang yang tidak bertanggung jawab untuk melakukan kejahatan siber (cyber crime). Salah satu isu yang menjadi tantangan besar dan permasalahan internasional saat ini adalah terorisme. Tindak terorisme ini bahkan telah dilakukan melalui teknologi dan termasuk dalam salah satu jenis cyber crime yaitu cyber terrorism. Kelompok teroris menjadikan sosial media sebagai salah satu media untuk menyebarkan propaganda teror mereka. Dalam menganalisis, metode yang digunakan oleh Penulis merupakan metode penelitian kualitatif. Metode ini lebih mengutamakan pada masalah proses dan makna/persepsi sehingga dapat mengungkap berbagai informasi kualitatif dengan deskriptif-analisis yang teliti dan tidak menolak informasi kuantitatif dalam bentuk angka maupun jumlah. Terhadap isu ini, penulis menyimpulkan sebuah konsep ASEAN Against Cyber Terorrism untuk menyelesaikan permasalahan yang ada. Karya tulis ini memberikan analisis yang lebih rinci terhadap dua poin penting. Pertama, terhadap mekanisme penyelesaian isu propaganda hitam yang disebarluaskan melalui media sosial yang saat ini dilakukan oleh ASEAN. Kedua, penjelasan dan implementasi konsep ASEAN Against Cyber Terorrism untuk diterapkan dalam mengatasi propaganda hitam oleh kelompok teroris melalui media sosial. Kata kunci: ASEAN; Cyber Terorrism; Media Sosial; Propaganda Hitam;